Religious Literacy In The PAI Curriculum In Madrasah - Sari, Windy Dian (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
The Curriculum of Islamic Religious Education (PAI) in Madrasah based on Religious Literacy can be referred to as a conceptual reality. This means that this idea is conceptual in nature. Therefore, what is referred to as Madrasah based on Religious Literacy is an attempt to describe how the concept of the PAI curriculum in Madrasah is based on religious literacy. It also explains that due to the conceptual crisis of Islamic Religious Education in Madrasah, which has moved further away from the values and cultural system of Salafi Islamic education, a conceptual solution is proposed that the appropriate Islamic Religious Education should be based on religious literacy. The research method used is a literature study by gathering data. Religious literacy in the PAI curriculum is highly essential for Madrasah students and it should start with research activities. This research aims to determine the implementation of religious literacy in the PAI curriculum in Madrasah. This research employs a qualitative approach. It is hoped that many Madrasahs will implement religious literacy in the PAI curriculum. Innovation, particularly in the PAI curriculum, should also incorporate religious literacy.